IN VITRO TEST: Antimicrobial Activity Potential From Ciplukan Fruit (Physalis minima L.) Extract in Methicillin-resistant Staphylococcus aureus (MRSA) - Muhammad Hanun Mahyuddin; Arifa Mustika; Gwenny Ichsan Prabowo; Deby Kusumaningrum (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
In Indonesia, in 2006 the prevalence of infections due to MRSA was 23.5%. Physalis minima L. plants are known to have antimicrobial activity because they contain compounds withaferin A which can induce programmed cell death. This research was to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of Ciplukan (Physalis minima L.) extract in Methicillin-resistant Staphylococcus aureus (MRSA) bacteria. Dilution test with Mueller-Hinton broth medium used for measuring the minimum inhibitory concentration (MIC). Ciplukan  fruit extract was dissolved in distilled water, and poured into a test tube with a certain concentration (0.9 g/mL (90%); 0.3 g/mL (45%); 0.15 g/mL (22.5%); 0.075 g/mL (11.25%) and 0.0375 g/mL (5.625%). After being incubated for 24 hours, the bacteria in the test tube were plated on nutrient agar plates, to determine the MBC. The MIC cannot be determined, because the solution in the dilution test tube is disturbed by the color of the extract so that turbidity cannot be observed. From the observations of the minimum bactericidal concentration MBC of the Ciplukan (Physalis minima  L.) fruit extract against MRSA was in the P1 tube or equivalent to 0.9 g / ml (90%).